Characterization of the affiliator’s competences of the Seguro Popular. An approximation of the Tabasco case. - Lopez Ronquillo, José Julio; Rodríguez-León, Alfonso; Castillo-Orueta, María Luisa (Horizonte Sanitario, 2019)
Objetive: to evaluate the types of skills needed to occupy the Seguro Popular affiliator place.Materials and methods: A descriptive and cross-sectional study carried out from October to November 2017 in the affiliation and orientation modules (AOM) of the municipality of Cárdenas, Tabasco, during which a mixed self-administered questionnaire was applied, based on the job profile of the AOM Procedures Manual (2006). The ABCD Alles model (2009) was used for the measurement scale, which evaluates the competences in degrees (maximum, expected, intermediate and minimum), adapting to the frequency of application. The universe was 26 affiliators.Results: Three types of competences were established (specific by area, cardinal, specific management) which eight competences were grouped: technical knowledge, initiative and effective communication, stress tolerance, teamwork, commitment to quality at work, flexibility and adaptability, planning and organizing, and leadership, people management and team management. The global average of degree of application in all the modules was 3.2, the maximum and expected degrees were the most frequent and the intermediate degree was presented in less frequency. The competence that presented the maximum degree of application was the initiative and effective communication.Conclusions: The staff modules is competent in an expected degree of application and their competences were reinforced, probably with the training received, may be one of the determining factors in the results obtained in this study. Keywords: Skills; Health services; health staff